Reducing the Incidence of Bullying in Secondary Schools - Gabrhelová, Gabriela; Pasternáková, Lenka; Barnová, Silvia (Emerging Science Journal, 2024)
The present study discusses the issues of bullying prevention in secondary schools with the objective of finding out about the efficiency of the experiential learning method in this context. Within a more extensive research study under realisation, the method of pedagogical experiment was applied to a sample of 100 vocational school students, and its partial results are presented. A set of experiential activities was prepared for teachers and used by them in the experimental group (50 students) within a 10-month bullying prevention program. In the control group (50 students), traditional methods of bullying prevention were used. To examine the effect of the intervention, the Olweus Bullying Questionnaire was administered to the participating students before and after the intervention (pre-test and post-test). The obtained research results suggest that the implementation of experiential learning activities contributed to a more positive school climate and favourable conditions for the realisation of bullying prevention in the participating school. Although given the limits of the research study, the present findings cannot be generalised to the entire population of vocational school students, the study brings unique data that fill the gap in current knowledge and create a basis for further research activities. Doi: 10.28991/ESJ-2024-SIED1-026 Full Text: PDF